Highly efficient and thermally stable fullerene-free organic solar cells based on a small molecule donor and acceptor. Issue 42 (12th October 2016) - Badgujar, Sachin; Song, Chang Eun; Oh, Sora; Shin, Won Suk; Moon, Sang-Jin; Lee, Jong-Cheol; Jung, In Hwan; Lee, Sang Kyu
Abstract : We studied fullerene-free organic solar cells using rhodanine-terminated BDT3TR and O-IDTBR. Abstract : We studied fullerene-free organic solar cells based on electron-donating (BDT3TR) and -accepting (O-IDTBR) small molecules. Bulk heterojunction devices comprising BDT3TR:O-IDTBR showed an excellent power conversion efficiency exceeding 7% and much better thermal stability than BDT3TR:PC70 BM devices after ageing at 120 °C for 300 hours.